Insulina pancreática de ratos diabéticos tipo 1 submetidos a um protocolo de treinamento físico individualizado - De Moura, Leandro Pereira [UNESP]; Gomes, Ricardo José [UNESP]; Leme, José Almeida [UNESP]; Voltarelli, Fabrício Azevedo [UNESP]; Ribeiro, Carla [UNESP]; De Moura, Rodrigo Ferreira [UNESP]; De Araújo, Michel Barbosa [UNESP]; Luciano, Eliete [UNESP]; De Mello, Maria Rostom [UNESP] (Desafio Singular, Lda, 2012)
Since diabetes mellitus is considered a world public health problem, the present study aimed to evaluate oral glucose tolerance (TTGo) and pancreatic insulin concentration (PIC) of type I diabetic rats subjected to an individualized exercise training protocol. A total of 40 adult Wistar rats were used, half of which induced to diabetes by alloxan (32 mg/kg) endovenous injection, and divided into four groups (10 per group): Sedentary Control (SC), Trained Control (TC), Sedentary Diabetic (SD) and Trained Diabetic (TD). The physical training consisted of swimming, 1 h/day, 5 days/week during 8 weeks, supporting overload equivalent to 90% of the individual anaerobic/aerobic metabolic transition determined at the beginning of the experiment. The rats of SD and TD groups presented body weight reduction in relation to controls, which was less accentuated in TD group. Water and food ingestion increased in the diabetic groups in relation to controls. The areas under the serum glucose curve during the GTTo of diabetic groups were higher than the controls. Physical training attenuated this elevation. The diabetic groups showed reduced PIC when compared to both control groups. The physical training protocol employed improved glucose homeostasis and attenuated the body weight loss of diabetic animals but did not alter pancreatic insulin concentration. © FTCD/FIP-MOC.
Pancreatic insulin of type i diabetic rats subjected to an individualized exercise-training protocol
Keywords: Diabetes mellitus; Pancreatic insulin; Physical training